Training quality - what is it and how can we improve it? - Bucher Sandbakk, S.; Walther, J.; Solli, G. S.; Tonnessen, E.; Haugen, T. (International Journal of Sports Physiology and Performance, 2023)
Sport science has provided detailed quantitative information about what successful athletes across multiple endurance sports do in their training to develop sport-specific physiological capacities and performance.1-4 Accordingly, our knowledge regarding the interplay of training-load factors such as duration, intensity, and frequency to stimulate the best possible adaptive responses has improved substantially. However, when coaches and athletes describe key factors leading to success, they often highlight how they work and why training practices are performed, indicating that the quality of the training process and execution of training sessions are key factors separating the best from the rest.3